Optimal transfection conditions and the safety profiles of dextran spermine/plasmid DNA as potential gene transfer vector to mouse airway. - Rosli, Rozita; Wendy-Yeo, W.Y.; Veerakumarasivam, Abhinanyu; Abdul Rahman, Sabariah; Domb, A. J.; Abdullah, Syahrilnizam (Malaysian Medical Association, 2010)
The emergence of gene therapy offers a new paradigm to the field of molecular medicine. However, current viral and non-viral gene transfer vectors are not efficient and often restricted by doselimiting toxicity. Thus, generation of a new gene delivery vector, which is efficient and with good safety profile is highly required. In this study, optimal transfection conditions and safety profile a novel biodegradable cationic polymerdextran-spermine (DSPM) in mouse airways were ascertained. The highest level of gene expression in the lungs of BALB/c mice was detected at D-SPM to plasmid DNA (pDNA) weight ratio (w/w) of 16, with 13.5 µg pDNA. No significant induction of pro-inflammatory cytokines in the broncho alveolar lavage fluids was observed, which implies no overt toxicity occurred in the mouse lungs. In short, these results demonstrate that D-SPM has moderate gene transfer efficiency but with acceptable safety profile in the mouse airways.